Strategi Brand Communication PT. Puncak Keemasan Dunamis Indonesia dalam Membangun Awareness terhadap Produk Animasi Beakbug - Dwijayanti, A A Istri Putri; Alit Suryawati, I Gusti Agung; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
Puncak Keemasan Dunamis Indonesia is a part of Holding Company Puncak Keemasan Group which is engaged in the field of animation industry with a vision to raise awareness of local content of Indonesian culture through animation products. Beakbug is the first animated brand of the company with the icon of Bali Starling which aims to lift the character of flora and fauna and also cultural traditions that exist in Indonesia. The purpose of this research is to find out how the brand communication strategy PT. Puncak Keemasan Dunamis Indonesia in building awareness of beakbug animation products. This research used descriptive qualitative approach. The result has been shown that the Brand Communication Strategy of PT. Puncak Keemasan Dunamis Indonesia in building awareness of beakbug animation product has been done by using Brand Visualization concept which consists of logo and Brand Activation consisting of Social Media Activation, Marketing Event Activation, Direct Marketing Activation, Promotion Activation, except Sponsorship Activation. Keywords : Animation, Beakbug, Brand Awareness, Strategy Brand Communication